Networking higher educational research for effective teaching in a developing country (2012)
Educational research and indeed any other type of research is multifarious and multi disciplinary, thereby involving multi-dimensional-approach, if any research exercise were to be efficiently and effectively conducted and to yiled meaningful and utilizable results. Networking educational research could make teaching more effective as findings from a networked research undertaking could be very meaningful and usable by a larger target group than would have been yielded by educational research undertaken solo. This is because a networked educational researching would invovle the mathamtics teacher, the science teacher/educator, the economics educator, the evaluator, the education manager among others who would synthesise their knowldege, attitude and skills together for synergy teaching and learning researching, which will in turn culminate in the sharing of knowledge and skills and in specialization in the process of the researching, resulting in gaining of experience and dexterity in the undertaking meaningful research exercise which would bring about improved teaching methodology and management simultaneously. Networked educational resarch must invovle the community which higher education serves whether local, national or international. The concomitant effect of a networked research would include cross-border or in interdisciplinary or multi-diciplinary broadening of improving teaching knowldege, skills, management and methodology. This is due to the fact that findings would be shared and applied by varied people and possibly from diverse climes; cost of undertaking the project could also be minimized than if it were undertaken solo or by a few partners; effectively disseminated findings would form basis for training those who did not participate in the undertaking, but who would apply these findings in routine teaching for improved learning.